Matrix degradation in osteoarthritis primes the superficial region of cartilage for mechanical damage. (15th September 2018) - Cooke, Megan E.; Lawless, Bernard M.; Jones, Simon W.; Grover, Liam M.
Graphical abstract: Abstract: Osteoarthritis (OA) is a degenerative disease that affects 25% of the world's population over fifty years of age. It is a chronic disease of the synovial joints, primarily the hip and knee. The main pathologies are degradation of the articular cartilage and changes to the subchondral bone, as a result of both mechanical wear and a locally elevated inflammatory state. This study compares the viscoelastic properties of cartilage that represents the biochemical changes in OA and age-matched healthy tissue. Further, the mechanical damage induced by this compressive loading cycle was characterised and the mechanism for it was investigated. The storage modulus of OA cartilage was shown to be significantly lower than that of healthy cartilage whilst having a higher capacity to hold water. Following mechanical testing, there was a significant increase in the surface roughness of OA cartilage. This change in surface structure occurred following a reduction in sulphated glycosaminoglycan content of the superficial region in OA, as seen by alcian blue staining and quantified by micro X-ray fluorescence. These findings are important in understanding how the chemical changes to cartilage matrix in OA influence its dynamic mechanical properties and structural integrity. Statement of significance: Cartilage has a very specialised tissue structure which acts to resist compressive loading. In osteoarthritis (OA), there is both mechanically- and chemically-induced damage to cartilage, resulting in severe degradation of the tissue. In this study we have undertaken a detailed mechanical and chemical analysis of macroscopically undamaged OA and healthy cartilage tissue. We have demonstrated, for the first time in human tissue, that the mechanical degradation of the tissue is attributed to a chemical change across the structure. In macroscopically undamaged OA tissue, there is a reduction in the elastic response of cartilage tissue and an associated destabilisation of the matrix that leaves it susceptible to damage. Understanding this allows us to better understand the progression of OA to design better therapeutic interventions.